ChemInform Abstract: A New Class of Squaramide‐Containing Phase‐Transfer Catalysts: Application to Asymmetric Fluorination of β‐Keto Esters. Issue 13 (March 2016) - Wang, Bin; He, Yingdong; Fu, Xuancheng; Wei, Zhonglin; Lin, Yingjie; Duan, Haifeng
Abstract: Several catalysts are synthesized and their efficiency in the asymmetric fluorination of keto esters is tested.